Wound Healing Activity of Ethyl Acetate Extract of Piper crocatum Leaves Combined with Geniotrigona thoracica Propolis - Dewi , Dea Puspita; Kustiawan, Paula Mariana (Program Studi Farmasi Universitas Mandala Waluya, 2025)
Wounds are a common health issue caused by various types of injuries, burns, or infections. Although several wound healing methods are available, many rely on synthetic chemicals that may have side effects. Therefore, there is a need for safer and more effective alternatives. Piper crocatum leaves and Geniotrigona thoracica propolis are known to contain flavonoid compounds that have the potential to accelerate wound healing naturally. However, limited research has explored the combination of these two substances to enhance wound healing effectiveness. This study aims to provide scientific evidence regarding the potential of the combination of ethyl acetate extract of P. crocatum leaves and G. thoracica propolis as a more effective, safe, and natural alternative for wound healing treatment. The research involved creating wounds on the backs of male rabbits, which were divided into seven groups. Each group received different treatments, including ethyl acetate extract of P. crocatum leaves and G. thoracica propolis, combinations of both (P1-P5), and a positive control (bioplacenton), while the negative control received no treatment. The preparations were applied topically, and wound healing was monitored daily. The results indicate that the combination of ethyl acetate extract of P. crocatum leaves and G. thoracica propolis (1:3) promoted faster wound healing compared to other combination.